Sugar apple seedling production as a function of substrates and slow-release fertilizer - Amorim, Scheila Antunes; Lima, Augusto Miguel N.; Cavalcante, Ítalo Herbert Lucena; Melo Júnior, Júlio César Ferreira de; Dias, Dayanne do Nascimento; Silva, Talison Sousa da; Silva, Kátia Araújo da (Comunicata Scientiae, 2020)
There is still a lack of studies on the effect of slow-release fertilizers and substrates on the production of high-quality sugar apple seedlings. In this context, the present study aimed to evaluate the quality and biomass of sugar apple seedlings grown in organic substrates at doses of slow-release fertilizer. The experimental design was randomized blocks in split-plot scheme, with four replicates and eleven plants per plot. Substrates were evaluated in the plots (fresh sugarcane bagasse; enriched sugarcane bagasse; coconut powder; commercial organic substrate Tropstrato®), whereas the doses of the slow-release fertilizer Osmocote® were evaluated in the subplots (0; 3; 6; 9; 12 and 15 kg m-3 of substrate). Substrates and slow-release fertilizer doses had effect on the formation of sugar apple seedlings. The effect of slow-release fertilizer is influenced by the substrate used in the formation of sugar apple seedlings. The substrate coconut powder showed the best performance for E%, NL and LAI in sugar apple plants, which reinforces its recommendation to be used in seedling production. For the studied conditions, based on the DQI, we recommend coconut powder associated with the slow-release fertilizer dose of 9 kg m-3 to produce sugar apple seedlings.